Diagnoses of Antarctic Inland Water Cycle Regime: Perspectives From Atmospheric Water Vapor Isotope Observations Along the Transect From Zhongshan Station to Dome A - Liu, Jingfeng; Du, Zhiheng; Zhang, Dongqi; Wang, Shimeng (Frontiers in Earth Science, 2022)
Accurate measurement of atmospheric water vapor isotopic composition of hydrogen and oxygen is required urgently for quantifying the atmosphere-snow isotope fractionation processes and identifying moisture source in Antarctic plateau region. This study presents in-situ real-time measurements of water vapor isotopes along the transect from Zhongshan station to Dome Argus (hereafter Dome A) in East Antarctica for the first time. The results present spatial variation characteristic of surface vapor stable isotopic composition, showing regular trend of gradual decrease of δ18O, δ D and high d-excess in interior plateau region, indicates significant δ18O-temperature correlation with a gradient of 1.61‰°/C and δ18O-altitude gradient of –2.13‰/100 m, similarly for δ D and d-excess. Besides, spatial variation of vapor isotopic composition implied three different regimes controlling the inland water cycle, it can divide as coastal steep area below 2000m, vast inland area with elevation varied between 2000 to 3000m, and high central plateau. Thirdly, observed high inland Antarctica water vapor d-excess quantitatively confirms stratosphere intrusion of air and vapor derived from low latitudes by Brewer–Dobson circulation. Another finding is the diurnal cycle signals of interior area water vapor isotopes δ18O, δ D, and air temperature, highlighted the substantial dominating role of supersaturation sublimation/condensation effect in inland and suggests that fractionation occurs during sublimation and that vapor–snow exchanges should no longer be considered insignificant for the isotopic composition of near-surface snow in Antarctica.